STUDENTS' SELF-EDUCATIONAL ACTIVITY IN CONDITIONS OF STATE STANDARD OF NEW GENERATION - Yuriy N. Pak; Irina O. Shilnikova; Dmitri Yu. Pak (Moscow Polytechnic University, 2016)
The article considers characteristic features of young specialist's self-education, shows students' self-dependent work motivation. There are defined the levels and types of students' self-dependent work. The article dwells on organization of students' self-dependent work and the problem matters relating to, reveals its key moments. Special attention is paid to redistribution of the teachers' and students' position in the present day educational process. There are given proposals in the field of methodological and methodical provision of students' self!dependent work.